PELATIHAN MEMBUAT INFOGRAFIS DENGAN APLIKASI CANVA BAGI APARAT DESA TAMANSARI, BOGOR - Iwan Setyawan; Junias Robert Gultom; Filda Angellia; Waskita Cahya; Aris Fatoni (Jurnal Abdi Insani, 2023)
The ease and speed of information provided by information technology have caused a gap between community expectations and the ability of the Tamansari Village Government, Bogor, to fulfill these expectations. First, the community expects fast information services from the village government. On the other hand, the Village Government is faced with the limited ability of village officials to provide information that can be conveyed quickly to the community. The Community Service Team intends to bridge this gap by improving the skills of Tamansari village officials, Bogor, in creating simple, engaging, and quickly distributed information. The method used is training in making infographics using the Canva application. As a result of this training, PKM partners, in this case, Tamansari Village officials, Bogor, were able to create infographics in the form of flyers regarding the requirements for processing Business Certificates (SKU) for Micro and Small Businesses. The flyers can then be distributed quickly via the WhatsApp application. With the skills to make information flyers, now Tamansari Village officials, Bogor can quickly convey information to community members. Thus, training in making infographics using the Canva application can be a solution to meeting citizens' expectations regarding the ease and speed of information services.